(untitled) (Marketing Journal, 2025)
This study analyzes the sustainable development of small business and private entrepreneurship in the Khorezm region, assesses the economic infrastructure, financial access, and regulatory environment at the regional level based on questionnaires and stati stical analysis methods. It also establishes that tax incentives and credit facilities support business development, but have negative effects such as bureaucratic obstacles and staff shortages, and thus justifies the need for systematic support for small business and private entrepreneurship, taking into account the regional characteristics of sustainable development. 360